Area of occurrence extension of Astyanax courensis Bertaco, Carvalho & Jerep, 2010, and Psalidodon goyanensis (Miranda-Ribeiro, 1944)(Characiformes: Acestrorhamphidae) with new records from tributaries in theStates of Goiás and the Federal District, Brazil - dos Santos Oliveira, Rayssa Nayara; Firmino, Artur; Slobodian, Veronica de Barros (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
In this study, we report new records of two freshwater fish species: Astyanax courensis and Psalidodon goyanensis. Both species are considered endemic to the Upper Tocantins river basin, with their known distribution originally restricted to the Chapada dos Veadeiros region in the State of Goiás, Brazil. The results of this study expand the known range of these species by documenting their presence in sub-basins located in both the Federal District and the State of Goiás, within the limits of the Upper Tocantins basin.